2014
DOI: 10.1586/17512433.2014.889562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of tapentadol extended-release in painful diabetic peripheral neuropathy

Abstract: Painful diabetic peripheral neuropathy is difficult to treat, partially because the underlying mechanism of pain is not fully understood. Various treatment guidelines recommend first-line agents, such as α2-δ ligands, serotonin-norepinephrine reuptake inhibitors, and tricyclic antidepressants but combination therapy of alternative agents including opiates is often warranted. Tapentadol extended-release has a novel dual mechanism of action; it is both a mu-opioid receptor agonist and a norephinephrine reuptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The treatment for painful diabetic peripheral neuropathy includes glycemic control and symptomatic pain management. Food and Drug Administration has approved only duloxetine, pregabalin and tapentadol for the treatment of painful diabetic neuropathy, but they have low efficacy and are able to cause serious side effects [3, 4]. The lack of an adequate pharmacological treatment supports the need to clarify better the diabetes-associated painful peripheral neuropathy pathogenesis to relieve this complication.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment for painful diabetic peripheral neuropathy includes glycemic control and symptomatic pain management. Food and Drug Administration has approved only duloxetine, pregabalin and tapentadol for the treatment of painful diabetic neuropathy, but they have low efficacy and are able to cause serious side effects [3, 4]. The lack of an adequate pharmacological treatment supports the need to clarify better the diabetes-associated painful peripheral neuropathy pathogenesis to relieve this complication.…”
Section: Introductionmentioning
confidence: 99%
“…The FDA approved the use of tapentadol for the treatment of diabetic neuropathic pain in 2012 due to its proved efficacy when compared to placebo. However, we still lack evidence of clinical relevance comparing tapentadol with first-line drugs, such as pregabalin, duloxetine, and tricyclic antidepressants 22,23 . Another use of tapentadol would be in acute pain after an outpatient surgical procedure.…”
Section: Contentsmentioning
confidence: 99%
“…Interestingly, the rates of constipation with maintenance therapy were reportedly the same. No study has evaluated the effect of tapentadol on neuropathic cancer-related pain [64].…”
Section: Is Tapentadol the Opioid Of Choice For The Elderly Or Frail mentioning
confidence: 99%
“…Studies have demonstrated the superiority of tapentadol over placebo, but no active comparators were included [64]. Patients included in these trials were opioid non-responders [64].…”
Section: Is Tapentadol the Opioid Of Choice For The Elderly Or Frail mentioning
confidence: 99%
See 1 more Smart Citation